Human rights of older persons: A new challenge for the 21st century in the universal system of the United Nations - Cisternas Reyes, Maria Soledad (Anuario de Derechos Humanos, 2018)
This monography focuses on specific aspects of equality and non-discrimination relating to older persons as well as on the forms of negligence, violence and abuse they may experience. Categories and levels are defined, accompanied by a wide range of cases taken from empiric evidence in each of the themes requested as inputs for the United Nations Open-Ended Working Group on Ageing. An extensive revision is also carried out of the United Nations international system for human rights promotion and protection, by identifying how older persons have been considered in the provisions of the United Nations different covenants and conventions, regarding matters such as equality, non-discrimination and protection against any form of negligence, violence and abuse, and, in general, in its contents applicable to older people. This article also discusses the 2030 Agenda and its relation to the human rights of older persons. Lastly, reflections and conclusions are included regarding the legal status of older persons within the current international system for the promotion and protection of human rights. At the end, the question is raised on whether there are concrete and specific advantages in place for States to enshrine the human rights model for older persons.